2010
DOI: 10.3113/fai.2010.0770
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness of the Second Metatarsal After Correction of Hallux Valgus

Abstract: The isolated cortical variations of the second metatarsal suggests that isolated hallux valgus correction led to a redistribution of the stresses on to the first ray.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There have been previous studies of human metacarpals and metatarsals using radiogrammetry to demonstrate cortical osteolysis in rheumatoid arthritis and after hallux valgus correction, respectively, but our study represents the first study of cortical osteolysis of metatarsals in participants with DMPN&CN. Our findings confirm the results of several studies, namely that aging results in the loss of cortical bone (eg, a reduced CCt.Wi and %Ct.Ar) that affects metatarsal strength estimates .…”
Section: Discussionmentioning
confidence: 80%
“…There have been previous studies of human metacarpals and metatarsals using radiogrammetry to demonstrate cortical osteolysis in rheumatoid arthritis and after hallux valgus correction, respectively, but our study represents the first study of cortical osteolysis of metatarsals in participants with DMPN&CN. Our findings confirm the results of several studies, namely that aging results in the loss of cortical bone (eg, a reduced CCt.Wi and %Ct.Ar) that affects metatarsal strength estimates .…”
Section: Discussionmentioning
confidence: 80%
“…HV‐related TM may be improved theoretically if we correct HV and bring the first metatarsal head to its optimal position. Opsomer et al [14] seemed to support this hypothesis. They studied 13 patients who had received surgery for isolated HV and measured the pre‐ and postoperative cortical thickness of the second and fourth metatarsal bones.…”
Section: Discussionmentioning
confidence: 92%
“…They studied 13 patients who had received surgery for isolated HV and measured the pre‐ and postoperative cortical thickness of the second and fourth metatarsal bones. They concluded that isolated cortical variations of the second metatarsal bone implied that isolated HV correction led to a redistribution of the stresses on to the first ray [14], and the decreased cortical thickness of the second metatarsal bone proved that lesser toe unloaded after HV correction. Some authors supported this conclusion and suggested that isolated HV corrective osteotomy was helpful for HV‐related TM.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness for the cortical bone ranged from 1.5 to 3 mm. This thickness was referred to in a previous study [ 22 ]. A hallux valgus deformity model was developed according to a preoperative radiograph from a study by Lee et al [ 23 ], which showed a 42° hallux valgus angle and a 17.4° intermetatarsal angle.…”
Section: Methodsmentioning
confidence: 99%